ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING SYSTEM DALAM PENENTUAN TARIF SEWA KAMAR HOTEL PADA JSI RESORT BOGOR - Hanipah Ali Sadikin; Muhamad Nur Afif; Yoyok Priyo Hutomo (Jurnal Cakrawala Ilmiah, 2024)
Competition for service companies operating in the hospitality sector is increasingly competitive. One way to maintain its existence is by setting room rental rates using the right method. The data sources used in this research are primary data and secondary data, namely data obtained directly including company documents. The data used in this research is where the author includes data related to the application of the activity based costing system method in determining hotel room rental rates, which includes traditional calculations and calculations using the ABC method. This research aims to determine the application of the ABC method in determining hotel room rental rates at JSI Resort Bogor. Based on the results of calculating hotel room rental rates using traditional calculations and the ABC method, it shows that in calculating the COGS for Cherokee rooms there is a difference of IDR 181,914 which is greater than the calculation using the ABC method. However, in the Willys, Sahara, Gladiator, Grand Gladiator, Rubicon, Brute and Hummer room types, there are differences in which the results of calculations using ABC are smaller or more effective than traditional calculations. There was a difference of up to Rp. 2,785,179 in the calculation of the basic price for determining rental rates because in the Activity based costing method, overhead costs for each product were charged to many cost drivers, resulting in accuracy and effectiveness in cost expenditure. Using the activity based costing (abc) system concept in determining hotel room rental rates can provide more accurate and more efficient cost calculation information.